Copy Number Table for Matched Primary and Locally Recurrent Breast Tumors - de Marchi, Tommaso (Lund University, 2023)
File reports table on copy number information for matched primary and locally recurrent breast tumors. "CN.table" reports copy number for each sample. "CN.DELTA.table" reports on paired sample copy number changes (CN delta = CN.recurrence - CN.primary) for each tumor pair.

This dataset was used for Figure 3 in the following manuscript:

"Proteogenomics decodes the evolution of human ipsilateral breast cancer". De Marchi T, Pyl PT, Sjöström M, Reinsbach SE, DiLorenzo S, Nystedt B, Tran L, Pekar G, Wärnberg F, Fredriksson I, Malmström P, Fernö M, Malmström L, Malmström J, Nimèus E. accepted for publication
Keywords: Proteomics and metabolomics; Genomics and transcriptomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik